E-commerce requirement analysis and design with Fogg Behavior Model (FBM) - Ahmad, Fauziah; Asmadi, Syafiyana Elysha; Janom, Norjansalika (Universiti Teknologi MARA, 2025)
E-commerce platforms often struggle to convert user visits into meaningful actions, and this paper explores how the Fogg Behavior Model (FBM) can be used to design a more effective e-commerce (EC) platform. FBM focuses on three key factors that influence user behavior: motivation, ability, and triggers. It offers a structured framework for designing systems that not only meet functional needs but also enhance user engagement and actions. The Web Development Life Cycle (WDLC) method was employed to develop an EC platform for Carro Empire, a small business enterprise that wanted to improve its EC platform to attract and expand its existing business. During the analysis and design stage of the WDLC methodology, FBM elements were incorporated as part of the EC development. It involved stakeholder interviews, thematic analysis, and content mapping of user needs to FBM elements during the analysis and was translated into user/stakeholder requirements and design. Motivation was addressed through features like 3D product views, customer reviews, and urgency cues; ability was enhanced via simplified navigation, search filters, and integrated payment options; and triggers were implemented through contextual prompts and real-time notifications. System models, including use case diagrams and UI mockups, were developed and validated by the business owner. A working prototype was developed, and positive feedback was received from the business owner, showing that FBM helps create a more user friendly and persuasive online shopping experience. This study helps to contribute to the field of persuasive system design by demonstrating how behavioral models can be practically applied in system development. For future work, the study recommends conducting user testing, such as surveys or A/B testing, to measure how FBM-based features impact customer behavior and improve the system further. The integration of advanced technologies such as WebGL for interactive 3D models is also recommended to further enhance user engagement.